MADRASAH DINIYAH SEBAGAI PUSAT PENDIDIKAN ISLAM DAN PEMBERDAYAAN MASYARAKAT UNTUK MENINGKATKAN KUALITAS HIDUP - Wala (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
This research is motivated by the crucial role of Madrasah Diniyah as an Islamic educational institution that not only teaches religious values but also contributes to community empowerment, thereby improving the quality of life. The purpose of this study is to analyze how Madrasah Diniyah functions as a center for education and socio-economic empowerment in a sustainable manner. The methodology used is a literature review that examines relevant studies on the roles, functions, and challenges of Madrasah Diniyah in a social context. The principal results highlight that Madrasah Diniyah effectively shapes students' character, empowers local economies, and strengthens social capital through community activities. The major contribution of this research is to affirm Madrasah Diniyah as a social change agent, integrating religious education with community empowerment, thereby positively impacting the sustainable improvement of quality of life. In conclusion, Madrasah Diniyah requires adequate policy support and resources to overcome challenges and promote innovation and synergy with various stakeholders for sustainable development.